Effect of Schizophrenia Care Application (Ics Mobile) on Family Knowledge about Activities Daily Living (ADL) to Schizophrenic Patients - Irfan I; Shelly Iskandar; efri widianti (Faculty of Nursing Universitas Padjadjaran, 2018)
Activities Daily Living (ADL) is the most common problem in schizophrenia. One most crucial effort is providing health education to families is considered useful in order to be able to increase family knowledge of the treatment process. The use of health education media can take advantage of the development of smartphone technology so as to make health education more interactive. Moreover, the ICS_Mobile application contains information about ADL through text and video. The purpose of this study was to determine the effect of ICS_Mobile application on family knowledge about Activities Daily Living (ADL) in schizophrenic patients. This study uses a quasi-experimental research method with pre-test and post-test control group approach. The population is 341 members of schizophrenia family with a sample of 40 respondents, divided into 2 groups, the intervention group 20 respondents and the control group 20 respondents. Sampling was collected by using purposive sampling. Respondents' knowledge was measured using instruments developed by researchers and content testing and construct test with Crombach'sAlpa value of 0.954. Data were analyzed using repeated measures ANOVA. The results showed that there was an increase in the mean score of knowledge after the intervention with the value (t = -14.079 p = 0,000), there was no significant increase in the average score of knowledge in the control group with the value (t = -1,751 p = 0,096), and there were differences the average knowledge between the control group and the intervention group with the value (t = 12,933 p = 0,000). The conclusion of this study that the provision of health education interventions using the ICS_Mobile application shows a significant influence on increasing family knowledge about Daily Living Activities (ADL) in schizophrenic patients. Researchers recommend the use of ICS_Mobile applications in health services as an option in increasing knowledge of schizophrenia treatment.Keywords: Activities daily living, ICS_Mobile, Knowledge, Schizophrenia, Smartphone